1989
DOI: 10.2466/pr0.1989.64.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Choice Behavior: The Logical Relation between Linear Objective Probability and Nonlinear Subjective Probability

Abstract: In choice behavior, researchers have noticed that humans have a preference for some probabilities, Most researchers in the past 40 yr. have been unable to account for the nonlinearity of this behavior. The convex shape of nonlinear subjective probabilities has been experimentally confirmed by every investigator from Preston and Baratta through Edwards, Handa, and Kahneman and Tversky. What has been lacking is a clear analysis of why the probabilities have a convex shape. Here, it is argued that Keynes provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Scholars have known for a long time that risk taking is not based on rational calculations alone [S], with even the great Lord Keynes, a highly successful speculator himself, arguing that taking risks requires optimism and what he quaintly, if obscurely, described as "animal spirits" [4]. Yet entrepreneurs' personality differences have found that such measures of animal spirits are weak predictors of risk taking [6] [18].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have known for a long time that risk taking is not based on rational calculations alone [S], with even the great Lord Keynes, a highly successful speculator himself, arguing that taking risks requires optimism and what he quaintly, if obscurely, described as "animal spirits" [4]. Yet entrepreneurs' personality differences have found that such measures of animal spirits are weak predictors of risk taking [6] [18].…”
Section: Introductionmentioning
confidence: 99%
“…But when lower than 1, the weight must be taken into account (note that the coefficient can be re-written as c D [p/(1 C q)][(2w/(1 C w)]). The distortion of p implied by a weight lower than 1 shows that Keynes's coefficient can account for what, after Ellsberg, has been termed ambiguity aversion (Brady and Lee 1989).…”
Section: Which Keynes For Understanding Decision-making Under Uncertamentioning
confidence: 99%
“…For instance, the famous example of the umbrella dilemma in the TP (Keynes 1973a, p. 32) is usually classified as a situation of non-comparable probabilities (Carabelli 1998). But it can also be understood as an example of conflicting evidence like in the current ambiguity literature (Cabantous 2007, Smithson 2008, and classified as something that makes decision in principle more cumbersome than under ambiguous evidence, but does not exclude that it can be made on some "rational" basis by skilled agents. 20 As already noted, this was represented by Keynes via the "risk" associated with trying to get a profit while taking part in a project that cannot yield it for sure, thus possibly originating a loss (Gerrard 2003).…”
mentioning
confidence: 98%
“…A,, where p, = .I, q , = .9, and A, = $900, a large majority of decision makers will choose emv, over ernv, if probability preferences are nonlinear. Only if probability preferences are linear will the decision maker be indifferent to emv, and ernv,.Brady and Lee (1989aLee ( , 1989bLee ( , 1989c demonstrated that the type of problem discussed above, called by Kahneman and Tversky the "certainty effect" and by other researchers the AUais paradox or security level problem, is easily handled by Keynes' decision rule.Unfortunately, Keynes, in his discussion of applied decision making in 'Request reprints from Dr. M. E. Brady, …”
mentioning
confidence: 99%
“…Brady and Lee (1989aLee ( , 1989bLee ( , 1989c demonstrated that the type of problem discussed above, called by Kahneman and Tversky the "certainty effect" and by other researchers the AUais paradox or security level problem, is easily handled by Keynes' decision rule.…”
mentioning
confidence: 99%